Development of Flood Forecasting Using Statistical Method in Four River Basins in Terengganu, Malaysia - Noor M.S.F.M.; Sidek L.M.; Basri H.; Husni M.M.M.; Jaafar A.S.; Kamaluddin M.H.; Majid W.H.A.W.A.; Mohammad A.H.; Osman S. (Institute of Physics Publishing, 2023)
Flood control; Forecasting; Case-studies; Critical region; East coast; Flood forecasting; High intensity; Malaysia; Northeast monsoon; River basins; Floods; climate forcing; flood forecasting; monsoon; precipitation intensity; river basin; statistical application; topography; water level; Malaysia; Terengganu; West Malaysia